TASK-BASED LANGUAGE TEACHING (TBLT): PRACTICAL APPLICATIONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the principles and practical applications of Task-Based Language Teaching (TBLT), a communicative approach to language learning that emphasizes the use of meaningful tasks over traditional grammar instruction. It outlines how TBLT can be implemented in the classroom through a structured three-phase process: pre-task, task cycle, and post-task. The article also provides examples of tasks suitable for different proficiency levels in ESL/EFL contexts, ranging from beginner to advanced learners. TBLT encourages authentic communication, collaborative learning, and learner autonomy while promoting both fluency and accuracy. It presents a learner-centered approach that integrates the focus on form as language naturally arises during tasks. The article concludes that TBLT effectively bridges the gap between classroom learning and real-world language use, enhancing learners' communicative competence.